Microgrids -A Future Smart Grid Design - Ms.Thrishna Jayaraj; Prof. G Justin Sunil Dhas (Journal of Power Electronics and Devices, 2018)
Microgrid is the small scale power grid with a bunch of manifold distributed generators (DGs) that supply electrical energy to consumers. The main components include loads, DERs, master controller, smart switches, protective devices, as well as communication, control and automation systems [1]. Two main control techniques used in microgrids are hierarchical control and distributed control structures. Both controls structures empower consistent and resourceful operation for microgrids. Different measures have been developed to improve the negative effects of the voltage disturbance and to moderate the power quality complications. A microgrid can able to operate moreover in grid- connected or autonomous (islanded) modes. Islanding can have undesirable impacts on system operation as well as safety issues if not detected and configured on time. Within the smartgrid concept microgrids have been proposed as novel distribution network architecture.